2019
DOI: 10.1111/nph.16137
|View full text |Cite
|
Sign up to set email alerts
|

Gazing into the anthosphere: considering how microbes influence floral evolution

Abstract: Summary The flower is the hallmark of angiosperms and its evolution is key to their diversification. As knowledge of ecological interactions between flowers and their microbial communities (the anthosphere) expands, it becomes increasingly important to consider the evolutionary impacts of these associations and their potential eco‐evolutionary dynamics. In this Viewpoint we synthesize current knowledge of the anthosphere within a multilevel selection framework and illustrate the potential for the extended flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 90 publications
0
50
0
Order By: Relevance
“…Rebolleda‐Gómez et al . (, in this issue pp. 1012–1020) further explore the interaction of the flower and its environment, in particular the microbial community that inhabits the flower.…”
Section: Ecology Of Plant Reproductive Systemsmentioning
confidence: 95%
“…Rebolleda‐Gómez et al . (, in this issue pp. 1012–1020) further explore the interaction of the flower and its environment, in particular the microbial community that inhabits the flower.…”
Section: Ecology Of Plant Reproductive Systemsmentioning
confidence: 95%
“…Mechanistically, local adaptation to abiotic environments or biotic interactions must ultimately be based on genetic differences in the expression of traits, yet biotic interactions themselves can alter the expression of traits. For example, microbiomes shape traits from obesity to life history in their animal hosts (Turnbaugh et al, 2008;Gould et al, 2018), and plant-microbiomes shape a comprehensive range of vegetative and floral traits in plants (Friesen et al, 2011;Rebolleda-Gómez et al, 2019). If one species' influence on another species' phenotype feeds back to affect its own fitness, selection will shape any genetic variation in the first species affecting traits in the second (so-called 'extended' phenotypes Dawkins et al, 1982;Rebolleda-Gómez et al, 2019;O'Brien et al, 2021).…”
Section: Plants and Biota Have Both Opposing And Aligned Effects On Traits Across Environmental Gradientsmentioning
confidence: 99%
“…by antagonizing phytopathogenic microorganisms), should not be overlooked [33,34]. In this way, the downstream effect of microbes in floral biology may have important consequences on plant-animal interactions, plant fitness and plant health [19,28,35], and eventually have a relevant impact on agriculture, ecosystem dynamics and plant conservation. Finally, flower-inhabiting fungi have a huge potential in industrial applications as demonstrated, for example, for second-generation bioethanol production [36].…”
Section: Why Is It Worth Studying Flower-inhabiting Fungi?mentioning
confidence: 99%